A emergência da criminalidade urbana violenta na sociedade moçambicana pós-colonial - Maloa, Joaquim Miranda (2019)
This doctoral thesis studies the relationship between crime, violence and conflict in the Modern Mozambican Society. This thesis aims to analyze the emergence of violent urban crime in the post-colonial Mozambican society. It was investigated through Historic sociology that way the practs of institutional violence and civil war of the years 1975-1990, Currently joins violent urban crime, about everything, to homicides, armed robberies and kidnappings that proved crucial to understanding the passage “of tingling crime or chicken pile”, for violent urban crime. By Between interviews, direct observation and journalistic reporting, it has been found that current forms of urban crime retain some traces of violence inherited from the period prior the 1990s. Finally, in order to portray the impact f violent urban crime, this research analyzed the social representations of police officers who have the powers to protect people, property, ensure respect for legality, guarantee order, security, tranquility and repress crime, are being hit by violent crimes. Asked what is the impact of it on this work and in mozambican society life.